Management of Bilateral Foreign Objects in Immature Permanent Maxillary Central Incisors: A Case Report - Chourasia, Hemant Ramesh (European Journal of General Dentistry, 2023)
Traumatic dental injuries are more commonly seen in children and it often results in a complicated crown fracture. This case is unique as foreign objects in the form of hand-sewing needles were accidentally lodged bilaterally in both maxillary central incisors. A 13-year-old patient was referred to the Dental Clinics at the College of Dentistry, Jazan University with a complaint of broken needles in her front teeth and a history of trauma 3 years ago. Although the patient had the habit of using a hand-sewing needle to remove the lodged food particles from the open pulp chamber, she was not able to recollect the incidence of needle separations. Radiographic examination revealed radiopaque objects in the middle third of the right maxillary central incisor (#11) and in the apical third of the left maxillary central incisor (#21). Tooth #11 was clinically diagnosed as pulp necrosis with chronic apical abscess and tooth #21 as pulp necrosis with asymptomatic apical periodontitis. The micro tweezer from the broken instrument removal kit (Zumax Medical Co.,Ltd., Jiangsu, China) was used to retrieve the separated needle pieces under the operating microscope. The open apices were managed by the formation of mineral trioxide aggregate apical plug, and the procedure of root reinforcement was achieved by bonded resin cement and fiber resin posts. Finally, teeth were restored with dual cure core build-up composite material and direct composite veneers. Recommendations are made to treat complicated crown fractures, especially in children on priority to minimize the risk of foreign object impaction.
Keywords: foreign object; hand-sewing; maxillary central incisors; needle; root canal